2020
DOI: 10.1590/0103-8478cr20180255
|View full text |Cite
|
Sign up to set email alerts
|

Sequential metabolizable energy plans for piglets from 7 to 30 kg

Abstract: The objective of this study was to evaluate sequential metabolizable energy (ME) plans, maintaining the lysine: calorie ratio for piglets from 7 to 30 kg. Forty eight female piglets with initial weight of 6.9 ± 1.2 kg and final weight of 30.5 ± 3.8 kg were randomly allocated in a randomized complete blocks design to three nutritional plans with eight replicates and two animals per experimental unit. Sequential plans provided four ME levels: plan 1: 3,300-3,250-3,200-3,150 kcal ME kg-1, plan 2: 3,400-3,350-3,30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…On the other hand, it was reported that the use of a nutritional plan consisting of 3. 40, 3.35, 3.30, and 3.25 Mcal ME kg −1 for piglets from 7 to 10 kg, 10 to 15 kg, 15 to 20 kg, and 20 to 30 kg, respectively, increased ADFI, ADG, and FW, and also improved feed conversion when compared with nutritional plans with lower ME levels (Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…On the other hand, it was reported that the use of a nutritional plan consisting of 3. 40, 3.35, 3.30, and 3.25 Mcal ME kg −1 for piglets from 7 to 10 kg, 10 to 15 kg, 15 to 20 kg, and 20 to 30 kg, respectively, increased ADFI, ADG, and FW, and also improved feed conversion when compared with nutritional plans with lower ME levels (Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…While older pigs have the ability to regulate feed intake according to their energy requirement (Noblet et al, 2001), there is evidence that weaned piglets do not have this control capacity yet, since studies have found that increasing the energy concentration of the diet can stimulate intake (Adebowale et al, 2019;Silva et al, 2020). There is also the hypothesis that for weaned piglets, due to their limited stomach capacity, the increased concentration of energy in the diet stimulates energy intake and increases weight gain (Oresanya et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that increase in dietary energy levels reduce diet intake, but without any effect on BW gain (Vieira et al, 2015). Conversely, other studies in the literature have shown that increases in dietary ME intensify BW gain in weaned piglets (Quiniou & Noblet, 2012;Silva et al, 2020). Differences found in these studies, are likely related to variations in the composition of dietary ingredients and manipulation of nutrient densities.…”
Section: Performancementioning
confidence: 88%